Clinicopathological features and prognosis assessment of extranodal follicular dendritic cell sarcoma - Li, Lan (World journal of gastroenterology : WJG, 2010)
AIM: To establish a model for prognosis assessment of extranodal follicular dendritic cell (FDC) sarcoma.METHODS: Nine lesions were examined by routine and molecular approaches.Clinicopathological factors from the new cases and 97 reported cases were analyzed for their prognostic values.RESULTS: The current lesions were found in f ive male and four female patients,located mainly in the head and neck area and averaging 7.2 cm in size.Six patients had recurrence or metastasis and three remained free of diseas...